Impact of ICT Training on Junior High School Teachers' Performance in Teaching Mathematics in Tamale Metropolis - Iddrisu, Bariham; Abdul Wadudu, Mohammed; Awolu, Fusheini (Advances in Social Sciences Research Journal, 2024)
This study employed a quasi-experimental research design to examine the influence of ICT training on the proficiency of mathematics educators after receiving instruction on incorporating Computer Aided Instruction (CAI) into their teaching and learning practices. The study also probed to determine if differences exist in the academic achievement of JHS students who were taught mathematics with CAI and those taught with Traditional Method of Instruction (TMI). Ten JHSs were randomly sampled where five schools served as experimental group and the remaining five as control group. Mathematics Achievement Test (MAT), Classroom Observation Schedules (COS), and questionnaires were employed to collect the data from teachers and students. Using SPSS version 20, the data was analyzed and presented in tables and graphs. The study's findings demonstrated a noteworthy enhancement in the proficiency of both teachers and students in mathematics subsequent to the ICT training. It was also discovered that ICT training had a statistically significant effect on the mathematics performance of both teachers and pupils, leading to a good conclusion. Lastly, teachers in the study area encountered obstacles such as a scarcity of ICT laboratories, the nonexistence of internet connectivity, and insufficient ICT resources. The study recommends the establishment of regional centers to train mathematics teachers on how to teach with ICT, supply laptops and computers to JHSs using the PPP model, and equip JHSs with digital content to support teaching and learning with technology.